2018
DOI: 10.1093/tbm/iby006
|View full text |Cite
|
Sign up to set email alerts
|

Posts, pics, or polls? Which post type generates the greatest engagement in a Facebook physical activity intervention?

Abstract: Social networking websites have attracted considerable attention as a delivery platform for physical activity interventions. Current evidence highlights a need to enhance user engagement with these interventions to actualize their potential. The purpose of this study was to determine which post type generates the most engagement from participants and whether engagement was related to change in physical activity in an intervention delivered via Facebook. Subgroup analysis of the intervention condition of a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
1
18
1
Order By: Relevance
“…User engagement is essential for the success of Web-based interventions [15], which can be influenced by content, moderators, and users themselves. A study examining user engagement between different types of Facebook posts (eg, pictures, polls, multimedia, and questions) found that posts requiring a simple response, particularly polls, generated the greatest engagement [35]. Similarly, in our study, moderator-initiated posts that offered simple questions and moderator follow-up comments did incite a response from users, suggesting that users felt comfortable engaging with content sourced directly from the moderator.…”
Section: Discussionsupporting
confidence: 59%
“…User engagement is essential for the success of Web-based interventions [15], which can be influenced by content, moderators, and users themselves. A study examining user engagement between different types of Facebook posts (eg, pictures, polls, multimedia, and questions) found that posts requiring a simple response, particularly polls, generated the greatest engagement [35]. Similarly, in our study, moderator-initiated posts that offered simple questions and moderator follow-up comments did incite a response from users, suggesting that users felt comfortable engaging with content sourced directly from the moderator.…”
Section: Discussionsupporting
confidence: 59%
“…Poll questions were less well received. This finding is in contrast to Edney et al ( 28 ), who described that Facebook posts with simple poll questions generated the highest engagement in a physical activity intervention. Lack of anonymity (e.g., the high proportion of participants who knew each other in any given community) could partially explain why Facebook posts containing polls/surveys were less well received in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Detailed characteristics of each study (n=19) [22,24,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], and each measure of association, are provided in Multimedia Appendix 5. All 19 studies (n=7776 participants) were of physical activity measures, with no study using measures of sedentary behavior.…”
Section: Study Characteristicsmentioning
confidence: 99%